Dr. J. Kevin Duplechain — Deep Plane Facelift — Lafayette - Duplechain, J. Kevin (DEEPPLANE™, 2026)
Surgeon profile record for Dr. J. Kevin Duplechain, practicing in Lafayette, USA. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003002; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; usa; lafayette